1987
DOI: 10.1016/0014-5793(87)81513-2
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of actin polymerization by latrunculin A

Abstract: Latr~ncul~n A, a toxin purified from the red sea sponge ~irun~~~~a rn~g~~~c~, was found previously to induce striking reversible changes in the morphology of mammalian cells in culture and to disrupt the organization of their m~cro~laments. We now provide evidence that latrunc~lin A affects the polymerization of pure actm in vitro in a manner consistent with the format~oa of a 1: 1 molar complex between latruneulin A and G-actin. The equilibrium dissociation constant (&) for the reaction in vitro is about 0.2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

25
618
2
3

Year Published

1999
1999
2012
2012

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 772 publications
(652 citation statements)
references
References 7 publications
25
618
2
3
Order By: Relevance
“…Unlike CB, LatA can bind specifically to G-actin and has no activity to block the barbed end of F-actin [25]. In addition, it was also reported that the LatA effect of cytoskeletal inhibition in mammalian cells was inactivated within 1 h when the cells were placed in fresh medium without LatA [24]. Thus, we consider that this rapid reorganization of cortical actin appears to have contributed to improvement of the blastocyst formation rate of SCNT embryos.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…Unlike CB, LatA can bind specifically to G-actin and has no activity to block the barbed end of F-actin [25]. In addition, it was also reported that the LatA effect of cytoskeletal inhibition in mammalian cells was inactivated within 1 h when the cells were placed in fresh medium without LatA [24]. Thus, we consider that this rapid reorganization of cortical actin appears to have contributed to improvement of the blastocyst formation rate of SCNT embryos.…”
Section: Discussionmentioning
confidence: 86%
“…After being washed twice with Hepes-TLP-PVA (Tyrode-lactate-pyruvate-polyvinyl alcohol) and the maturation medium, respectively, COCs with compact cumulus cells and evenly granulated ooplasm were used for the experiments. COCs (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) were cultured in a droplet of maturation medium (200 µl) under paraffin oil (Nacalai Tesque, Kyoto, Japan) in a polystyrene dish (35-mm: Becton Dickinson Labware, Oxnard, CA, USA) and cultured at 38.5 C in an atmosphere of 5% CO 2 in air. The maturation medium was TCM-199 with Earle's salts (Gibco, BRL, Grand Island, NY, USA) supplemented with 0.91 mM sodium pyruvate (Sigma-Aldrich Chemical, St. Louis, MO, USA), 3.05 mM glucose (Wako Pure Chemical Industries, Osaka, Japan), 0.57 mM cysteine hydrochloride hydrate (Sigma), 10 ng/ml epidermal growth factor (Sigma), 10 IU/ml eCG (ASKA Pharmaceutical, Tokyo, Japan), 10 IU/ml hCG (ASKA), 100 µg/ml amikacin sulfate (Meiji Seika, Tokyo, Japan) and 10% (v/v) pig follicular fluid.…”
Section: In Vitro Maturation Of Oocytesmentioning
confidence: 99%
See 2 more Smart Citations
“…Actually, they reversibly disrupt microfilaments of cultured cells at submicromolar concentrations (Spector et al 1983). Latrunculin A binds to G-actin in a molar ratio of 1:1 with a K d value of 0.24 μM and sequesters G-actin from actin polymerization (Coué et al 1987). Since latrunculin A has no severing effect (Saito et al unpublished observation), its action seems similar to that of monomer-binding proteins such as thymosin β 4 or DNase I.…”
Section: Latrunculinsmentioning
confidence: 99%